ChemInform Abstract: Alkane Catalytic Functionalization by Carbene or Nitrene Insertion Reactions. Issue 11 (8th March 2013) - Diaz‐Requejo, M. Mar; Caballero, Ana; Fructos, Manuel R.; Perez, Pedro J.
Abstract Review: 131 refs.